Analytical Study of the Viewpoints of the Jurists about the Rulings of Imitation and its Types - Allah Ditta; Asmatullah (Journal of Islamic and Religious Studies, 2018)
Today, majority of the Muslims' lives have turned out to be colored with a similar shade of the western civilization in every sphere of life. We watch that the matter of imitation achieved its most exceedingly awful pinnacle. In this era of ecstasy, the imitation of infidels and penitence of the Sunnah is growing rapidly due to the fact that Muslims have made it their habit. A particular group considers it enlightenment and ideological freedom and feels ashamed to follow Islam and Sunnah. The main reason for this attitude is that Muslims are unaware of the disadvantages of the imitation of infidels. In this article, the nuisances and flaws of imitation have been discussed, so that the Muslims could know about its imperfections and follow the Qur’ān and Sunnah.